An Analysis of Work-Related Musculoskeletal Disorders Among Butchers in Kano Metropolis, Nigeria - Bashir Kaka; Opeyemi A. Idowu; Henrietta O. Fawole; Ade F. Adeniyi; Omoyemi O. Ogwumike; Mark T. Toryila (Elsevier, 2016)
Background: Butchering is often associated with high rates of work-related musculoskeletal disorders (WRMSDs). However, published work on the prevalence of WRMSDs among butchers in Nigeria is scarce. This is important because meat processing practices differ across geographical and cultural locations. This study was therefore aimed at analyzing WRMSDs among butchers in Kano metropolis. Methods: Sociodemographic and work-settings information was obtained from 102 male cattle butchers (age, 37.49 ± 11.68 years) through survey. Information on the prevalence and pattern of musculoskeletal disorders was obtained from the respondents using the Standardized Nordic Questionnaire. Additional information on health seeking practices was also obtained using a pro forma. Associations between the prevalence of WRMSDs and each of the sociodemographic data and work settings were explored using Chi-square analysis. The level of significance was set at p < 0.05. Results: The 12-month and point prevalence rates of WRMSDs among butchers in this study were 88.2% and 74.5%, respectively. Whereas lower back complaints (66.7%) were the overall and lower body quadrant's most commonly reported WRMSDs among the butchers surveyed, wrist/hand complaints were the leading upper quadrant's (45.1%) most commonly reported WRMSDs among the respondents. There were significant associations between age and majority of WRMSDs in the body regions. Only 23.3% of the 90 individuals who had WRMSD visited the hospital to seek redress for their WRMSD. Conclusion: The prevalence of WRMSDs is high among butchers in Kano Metropolis. Few individuals with WRMSD utilize healthcare facilities. Age is a major risk factor in this setting.